APPLIED RISK MANAGEMENT IN CONSTRUCTION INDUSTRY: A REVIEW - Pooworakulchai, Chaiwat (International Journal of Engineering Technologies and Management Research, 2018)
Risk management was applied to many organizations. There was a risk of multiple and complex manner in the construction industry, because it has a variety of elements. The application of risk management was therefore used in solving problems that suffer from the past to create an alternative to proper functioning under conditions. This article studied the main application to risk management in the construction industry by the sample texts document. The applying of risk management in the construction industry was 3 stages of risk management which were the risk analysis, risk assessment, risk control and follow-up, which was used to store information in the past and brainstorm by virtue of experience, expert tips and techniques to determine the risk analysis and risk evaluation of a mathematical methodology combined with the master planning of construction work to analyze, evaluate the risk under different condition and situations. Control, risk monitoring and risk assessment were a small amount so it should be a topic of research in future rely on notes and update the plan. The three important things for the applying of risk management in the construction industry were personnel, information and continuous learning.